PENATALAKSAAN HOLISTIK PADA PASIEN TINEA KAPITIS MELALUI PENDEKATAN KEDOKTERAN KELUARGA - Lantani Nafisah Heviana; Reni Zuraida (CV. Jasa Sukses Abadi, 2021)
Dermatophytosis is a disease cause by the colonization of dermatophyte fungi that attack keratin-containing tissues such as the stratum corneum of the skin, hair and nails in humans. The prevalence of dermatophytosis in Asia reaches 35,6%. In Indonesia, dermatophytosis is 52% of all dermatomycoses, which is most are tinea cruris and tinea corporis. The study was Case Report study. Primary data is obtained through history taking and physical examination by making home visit, filling out family folders, and filling in patient files. Assesment is carried based on the initial holistic diagnosis, process, and end of the visit quantitatively and qualitatively. Lack of patient knowledge about the disease and poor personal hygiene of patient are the main internal risk factors causing patient to have gray patch type of Tinea capitis. The intervention that was given is education and counseling of the patient and patient family about matters that must be modified and the prevention about the disease. The intervention divided into patient center, family focus and community oriented. After holistic intervention with educational and counseling methods, there are decrease in clinical symptoms and behavioral changes was obtained by maintaining personal hygiene and the environment